2013
DOI: 10.1038/bcj.2013.61
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG-PET/CT imaging in an IL-6- and MYC-driven mouse model of human multiple myeloma affords objective evaluation of plasma cell tumor progression and therapeutic response to the proteasome inhibitor ixazomib

Abstract: 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) and computed tomography (CT) are useful imaging modalities for evaluating tumor progression and treatment responses in genetically engineered mouse models of solid human cancers, but the potential of integrated FDG-PET/CT for assessing tumor development and new interventions in transgenic mouse models of human blood cancers such as multiple myeloma (MM) has not been demonstrated. Here we use BALB/c mice that contain the newly developed iMycΔEμ gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 50 publications
(62 reference statements)
3
30
0
Order By: Relevance
“…4). In agreement with that, all three iMyc alleles collaborate effectively with enforced IL-6 expression (H2-L d -IL6 transgene) in malignant plasma-cell transformation [90, 91]. Indeed, the double-transgenic iMycIL-6 strains of mice provide a robust experimental model system characterized by short time to tumor onset and complete penetrance of the malignant phenotype (100 % tumor incidence) that is now available for preclinical studies on IL-6-targeted therapies in myeloma.…”
Section: Il-6-dependent Plasma-cell Tumors (Pcts) In Laboratory Micesupporting
confidence: 54%
See 1 more Smart Citation
“…4). In agreement with that, all three iMyc alleles collaborate effectively with enforced IL-6 expression (H2-L d -IL6 transgene) in malignant plasma-cell transformation [90, 91]. Indeed, the double-transgenic iMycIL-6 strains of mice provide a robust experimental model system characterized by short time to tumor onset and complete penetrance of the malignant phenotype (100 % tumor incidence) that is now available for preclinical studies on IL-6-targeted therapies in myeloma.…”
Section: Il-6-dependent Plasma-cell Tumors (Pcts) In Laboratory Micesupporting
confidence: 54%
“…Transfer of the iMyc transgenes from the original, mixed genetic background of segregating C57BL/6 × 129/SvJ alleles to the C background resulted in hypersusceptibility to inflammation-induced PCT. One of the newly developed, double-transgenic strains of iMycIL-6 mice, which was investigated in greater depth, is prone to myeloma bone disease [91], a shortcoming of many previously developed GEMMs of human myeloma. We are currently employing this strain to continue with the IL-6 theme, which includes a study on the biological significance of autocrine versus paracrine sources of IL-6 in tumor development (Fig.…”
Section: Accelerated Transgenic Mouse Models Of Il-6-driven Pctmentioning
confidence: 99%
“…These findings demonstrated that host priming (lethal vs. sub-lethal irradiation) is key for . Extra-medullary tumor load was modest ( Figure 1F) relative to mice harboring IL-6/MYC-driven PCNs for which comparable PET data were available [11]. In keeping with the large M-spikes presented in Figure 1E, the PET results indicated that the malignant PCs exhibit a myeloma-like preponderance for hematopoietic bone marrow.…”
supporting
confidence: 59%
“…Because our chief interest concerns improved preclinical modeling of myeloma, the followup investigations concentrated on the PCN-bearing mice. To evaluate tumor burden, tumor dissemination pattern and extent of extra-medullary disease, 18 F-FDG-PET imaging was used [11]. Extra-medullary tumor load was modest ( Figure 1F) relative to mice harboring IL-6/MYC-driven PCNs for which comparable PET data were available [11].…”
mentioning
confidence: 99%
“…43 Interestingly, 18 F-FDG-PET/CT imaging can be used to monitor tumor progression and response to treatment in this model. 44 Rearrangements of MYC are late progression events in MM that are found in B40% of advanced MM tumors and have welldefined roles in a number of tumor types. Early attempts at forcing MYC expression, such as those using the Em enhancer, which drives transgene expression throughout the B-cell development (Em-Myc transgenic model 45 ), resulted in the development of pre-germinal center lymphomas early in life.…”
Section: The Immunocompetent 5tmm (5t Radl) Modelmentioning
confidence: 99%